Pemberdayaan Pemuda Melalui Organisasi Kepemudaan Di Desa Dewasari Kecamatan Cijeungjing Kabupaten Ciamis - Liesdiana Yane Sujani; Regi Refian Garis; Ii Sujai (PAPSEL Research and Consulting, 2024)
Empowerment of Youth through Karang Taruna Organization in Dewasari Village, Cijeungjing Sub-District, Ciamis Regency. This research aims to evaluate youth empowerment through Karang Taruna in Dewasari Village, Cijeungjing Sub-District, Ciamis Regency. The research method employed was qualitative with a descriptive approach, involving 12 informants including village officials and Karang Taruna administrators. The findings indicate that youth empowerment by Karang Taruna in Dewasari Village has been initiated but not yet optimal according to empowerment theory. Challenges identified include low youth interest in training, lack of awareness about the importance of organizations, and constraints in entrepreneurship and funding. Efforts to address these barriers involve more intensive approaches, enhanced socialization and networking, and knowledge enhancement through seminars, workshops, and training sessions. Additionally, providing financial support is crucial to enhance empowerment effectiveness. This study provides insights into real challenges faced in enhancing youth participation in community development. By implementing appropriate strategies, it is expected that youth empowerment through Karang Taruna will become more effective and significantly contribute to Dewasari village's progress.